Sistem Informasi Penerimaan Siswa Baru Berbasis Web Dengan Fasilitas SMS Gateway SMA Negeri 1 Pajangan - KHASANAH, Abanja Nur Alfa ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of information technology for the past few time, so it has offered the society to take advantage of its easiness. Acceptance of new student is a rountine activity every year in each school, especially in SMA Negeri 1 Pajangan. This SMA still uses procedures for its enrolment, such as purchasing the enrolment form, returning the completed form, see the announcements at school, while the committee made a note and organizing them using Microsoft Excel. This acceptance of new student information system bases on web with gateway SMS facility SMA Negeri 1 Pajangan made for give easier to prospective students and new admissions committee. This system use pure PHP programming language, MySQL for manage database, and gammu for gateway SMS facility. This system is designed for manage prospective students data, parents data, grades SKHUN data. The prospective student registering ang then complete data on website, the last they can see announcement of acceptance via SMS service or website.